Efektifitas Komunikasi Ustadz Sudiyo Dalam Meningkatkan Pemahaman Ajaran Islam Bagi Jama’ah Masjid Jami At-Taqwa Kalibaru, Cilodong, Kota Depok - Yoki Rizkiyo Maulidan; Nirwan Syafrin; Oking Setia Priyatna (Universitas Pahlawan Tuanku Tambusai, 2024)
The effectiveness of da'wah with all accurate activities can run efficiently and even become a driving force for change in the community for the better, if packaged in clear and systematic ways and methods. Therefore, to carry out da'wah activities, responsive methods are needed using straightforward, interesting and wise language so that communication becomes interesting. This research aims to find out how effective the ustadz's communication is in improving Islamic teachings for the Jami At-taqwa Mosque congregation. And I want to know the understanding of the congregation after and before listening to Ustadz's lecture. This research approach uses descriptive qualitative, because this research explains phenomena that occur in the field by collecting data obtained from research informants. The data collection techniques used in this research were observation, in-depth interviews and documentation. The research results found by researchers were as follows, using a lecture method that was easy to understand and accepted by the congregation. This method makes it easy for the congregation to learn Islamic teachings, so that the congregation is happy to always attend Friday night recitations at the Jami At-taqwa Mosque, Kalibaru, Cilodong, Depok City.